Using the Podcast Contents to Help EFL Students in Improving Their Grammar and Pronunciation - Edy Suseno (CV. Tripe Konsultan, 2023)
The study aims to determine how the teacher uses podcast resources to improve the students' grammar and pronunciation learning. Many EFL students struggle to use good grammar and practice pronunciation. By addressing their weaknesses, they needed to hone their public speaking abilities. To accomplish this, twelve college students joined a treatment program that used podcasts to address this problem. The teacher created a social media group to facilitate the teaching and learning process and to improve the learning of the online course materials. After finishing it, he instructed students on how to study grammar while bilingual. The students finished the lecture and the assignment in both languages. The teacher posted a URL on a forum to help the students more naturally understand grammar usage. The students click on, and a podcast page appears on their screen. To hear the speaker's voice, they push the play button. They read the transcript as they listened to the voice. They concentrated on getting the transcript done. The corresponding grammatical content was looked for in each line of the text. The words and phrases related to the grammar being studied were highlighted. they visualized uploading their work. The instructor then requested that the students read the transcript aloud for recording and upload. The teacher then evaluated all of the uploaded work in order to offer comments. The information was acquired by keeping an eye on the teaching-learning process. The conclusion was then reached after qualitative analysis. According to the study, podcasts can improve pronunciation and structure learning. The teachers can use the findings to teach connected disciplines. The other researchers can also complete the further related work.